Custo Direto do Tratamento do Acidente Vascular Cerebral Isquêmico na Perspectiva de um Hospital Público Terciário (Direct Cost of Treating Ischemic Stroke From the Perspective of a Tertiary Public Hospital) - de Almeida, Juliana Tereza Coneglian [UNESP] (2024)
Objectives: To measure the direct cost of treating acute ischemic stroke (IS) from the perspective of a public hospital in Brazil (HCFMB) and compare it with the reimbursement by the Unified Health System (SUS), through the Procedure Table Management System, Medicines, Orthoses/Prostheses and Special Materials of the Unified Health System (SIGTAP). Methods: We performed a micro-costing study; four scenarios were evaluated: standard (1); alteplase (2); alteplase and mechanical thrombectomy (3); mechanical thrombectomy (4). Based on the number of patients hospitalized for ischemic stroke in 2019, hospital cost, and SUS billing were calculated for each scenario. Hospital costs were adjusted for inflation using CCEMG-EPPI-Centre Cost Converter. Results: In 2019, 258 patients were hospitalized due to IS, 89.5% in scenario 1, 8% in scenario 2, 1.5% in scenario 3, 1% in scenario 4. From the hospital's perspective, the cost per patient was estimated at R$7780.13, R$15 741.23, R$28 988.49, R$25 739.79, for scenarios 1, 2, 3 and 4, respectively. The reimbursement by SIGTAP was estimated at R$3079.87, R$5417.21, R$10 901.92, R$10 286.28, respectively. If thrombectomy had been included in the SIGTAP, the last two values would be R$25 393.34 and R$24 248.89. Conclusions: The hospital cost of treating acute IS in 2019 was estimated at R$2 295 209, the SUS reimbursement at R$889 391.54. With the inclusion of thrombectomy at SIGTAP, this reimbursement would be R$975 282.44, and the loss in the cost of HCFMB per patient in relation to reimbursement by the SUS is greater in scenarios without this procedure.